Mulching effect on soil organic carbon, yield and physiological characteristics of seed potato (Solanum tuberosum L.) plants - Babak Darvishi; Mehrdad Jenab; Rahman Bakhtar; Jahanbakhsh Hoseininejadian (علوم و فناوری بذر ایران)
This study was set up to survey the possibility of mulch utilization in water use management and to evaluate its effect on quality and quantity of potato seed tubers. A split plot factorial experiment based on randomized complete block design with 3 replications was conducted in 2 locations (Ardabil and Esfahan) and at 2 years (2013-14 and 2014-15). Main factor was Irrigation regime (Control and Mild Drought Stress) and sub factors were Variety (Agria, Arinda and Sante) and Mulch (Control, Wood chips, Straw and Compost of municipal waste). Results showed that under Mild drought stress, mulch (especially straw) significantly increased tuber number per unit area, while did not affect yield. Mild drought stress significantly reduced the number of established plants of Agria cv., hence straw mulch significantly increased established plants number of this cultivar under drought stress. Mild drought stress significantly reduced tuber size in Arinda cv. and straw or wood chips mulch significantly increased tuber size of this cultivar under drought stress. Organic mulch significantly increased soil organic carbon while compost of municipal waste decreased the amount of soil organic carbon by 17.1 percent